Assessment of a novel lung sealant for performing endoscopic volume reduction therapy in patients with advanced emphysema - Herth, Felix; Eberhardt, Ralf; Ingenito, Edward P.; Gompelmann, Daniela (Expert review of medical devices, 2011)
AeriSeal® Emphysematous Lung Sealant is a novel endoscopic lung-volume reduction therapy designed to reduce hyperinflation and improve pulmonary function and quality of life in patients with advanced emphysema. The device is administered to the subsegmental bronchus via a catheter as a 20 ml volume of liquid-foam. It flows into the peripheral airways and alveoli where it polymerizes and functions as a tissue glue, forming a film of material on the lung surface that seals the target region to cause durable absorption atelectasis. The AeriSeal System received CE mark approval for the treatment of patients with advanced upper lobe predominant and homogeneous emphysema based upon favorable results from clinical studies, and is commercially available in Europe. Patient and treatment site selection algorithms have been developed to simplify product use and optimize outcomes. This manuscript summarizes how the device is used, its mechanism of action and clinical trial results supporting its safety and efficacy.